Diagnostic of agro-industrial competitiveness in the department of Boyacá for 2011 - Becerra Gualdrón, Claudia Jessenia; Cruz Vásquez, José Luis (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The purpose of this paper is to identify the state of agro-industrial competitiveness in the Department of Boyacá. To carry this out, the variables of productivity and competitiveness were considered along with the factors of production and marketing. Also, technology, innovation and knowledge management applied by companies were taken into account. To identify the above features, a survey, which was administered to 106 agro-businesses in the Department of Boyacá, was applied in 2011. It was concluded that in general terms the current situation in the sector is not unfavorable, however, companies are not considering elements such as: marketing, investment in research, innovation and qualified personnel, and the standardization of processes. Also, expertise from universities is not usable and technological resources are very limited, which in the middle and long term threatens both the current position and the survival of the agro-industrial sector.